Subcritical and supercritical fluid extraction a critical review of its analytical usefulness - Mustapa, A. N.; Abdul Manan, Zainuddin; Mohd. Azizi, C. Y. (Faculty of Chemical Engineering & Natural Resources, 2008)
Subcritical R134a is suggested as a low-pressure alternative to supercritical CO2 in the supercritical fluid extraction technology in particular of palm oil application. Therefore, a measurement of solubility of palm oil in subcritical Rl34a will be carried out at temperatures of 40, 60, 70 and 80°C and pressures up to 300 bar. The solubility of carotene are also will be measured using UV Spectrophotometer. Results obtained from this study will be compared with the previous work and for the first time, simulation for the SFE process of palm oil will be performed using Artificial Neural Network (ANN) and it will be implemented in comparisons as well when the operating conditions of the previous findings are different from this study. It is expected that the solubility of the palm oil in subcritical Rl34a is much higher than SC-C02, and it is expected that R134a could be a viable alternative solvent to supercritical carbon dioxide as R134a could be perform well at a lower pressure used whereas can achieved a higher solubility compared to SC-C02